Is this the end of the conventional advertising in TV broadcasting? - Lange, Talvani (Contemporanea, 2010)
In this essay we explore some basic historical and economic aspects related to the TV advertising industry. Our main goal is to focus on old and new commercial formats that were created with the TV popularization in western societies in general. In this context we approach the promotional tool of product placement as a controversial marketing strategy, mainly if codes of advertising standards are considered to be followed by professionals in this field. Ethical directions to conceive advertising can be rethought after analysing promotional practices in broadcasting. Bibliographical research and discourse analysis, concerning these technological changes, were used as part of the methodology.